Factors associated to treatment adherence in elderly people with hypertension: A cross-sectional study in Ho Chi Minh city - Cao Nguyen Hoai Thuong; Tran Thien Thuan; Vo Thi Xuan Hanh; Ho Nguyen Anh Tuan; Tran Ngoc Dang (Elsevier, 2022)
Background: Treatment of hypertension should be continuous, and patients should be closely monitored for treatment adherence. However, non-compliance still exists globally. This study aimed to determine treatment adherence among patients aged ≥60 years with hypertension and its associated factors in an urban district of Ho Chi Minh City, Vietnam. Methods: A cross-sectional study evaluated treatment adherence in two areas: medication and non-pharmacological adherence. Medication adherence was measured using the 8-item Morisky Medication Adherence Scale. Non-pharmacological adherence was based on the Ministry of Health guidelines for hypertension treatment and assessed by lifestyle changes, including smoking cessation, alcohol consumption restriction, reduced salt intake, increased physical activity, and regular follow-up visits. Results: A total of 537 people participated in the study, of whom females accounted for the majority (63.7%), and patients aged 60-70 years old accounted for 50%. The proportion of patients with medication adherence was 11.7%. The percentages of patients who adhered to non-smoking and limited alcohol intake were 93.5% and 92.9%, respectively. A total of 76.9% of patients underwent regular check-ups. The proportion of patients who adhered to moderate and high levels of physical activity was 64.3%. Patients who were compliant with salt intake reduction accounted for 63.1%. Factors related to antihypertensive drug adherence included disease duration and chronic comorbidities. Factors associated with non-drug adherence included health insurance, comorbidities, and nutritional status. Conclusions: Intervention programs to increase hypertension treatment adherence among elderly patients should focus on educating drug adherence and salt reduction, especially in long-standing and comorbidities patients.